Implementation of a Standardized Patient Safety Checklist in Ophthalmic Surgery - Boese, Erin A.; Lee, Paul P.; Greenberg, Grant M.; Harrison, Richard V.; Weizer, Jennifer S. (Journal of Academic Ophthalmology, 2018)
Objective To develop and institute a standardized ophthalmology-specific operating room checklist, and to test adherence to the surgical checklist components after implementation.Design An ophthalmology-specific operative room checklist was developed using recommendations from surgical preoperative checklists from other subspecialties and checklists specific to cataract surgery. This standardized checklist was then implemented into the operating rooms. Operative room staff was trained on its use. Adherence to the checklist was measured prospectively.Setting Surgical centers at Kellogg Eye Center in Ann Arbor and Livonia, Michigan.Participants Patients undergoing ophthalmic surgery at the Livonia and Ann Arbor surgical centers.Main Outcome(s) and Measure(s) The primary outcome measures were surgical team adherence to each category of the operative checklist (preop, prebrief, preanesthesia verification, time-out, intraocular lens measurement/confirmation for cataract cases, debrief). Adherence to the subsections of the operative checklist was measured during three periods over the course of 1 year: baseline, postintervention (after introduction of the checklist in all operating rooms), and postadjustment (after additional training was provided to operating room staff and incentives to collect data were provided to personnel responsible for collecting it).Results A total of 2,532 surgical cases were included in the analysis. Baseline adherence ranged from 87 to 90% across preop, prebrief, preanesthesia, and time-out verification sections of the operative checklist. After the institution of the intervention and adjustments, adherence to the surgical checklist improved significantly across all areas of the checklist to 97–98% (p < 0.01).Conclusions and Relevance The development and implementation of an ophthalmology-specific operative room checklist increase adherence to recommended safety checks prior to the start of surgery. To maximize patient safety, the same or similar checklist is recommended for use in all ophthalmology operating rooms.
Keywords: surgical checklist; patient safety; time-out